2014
DOI: 10.4085/1062-6050-49.3.29
|View full text |Cite
|
Sign up to set email alerts
|

Altered Knee and Ankle Kinematics During Squatting in Those With Limited Weight-Bearing–Lunge Ankle-Dorsiflexion Range of Motion

Abstract: Greater ankle DF-ROM assessed during the WBL was associated with greater knee-flexion and ankle-DF displacement during both squatting tasks as well as greater knee-varus displacement during the single-legged squat. Assessment of ankle DF-ROM using the WBL provided important insight into compensatory movement patterns during squatting, whereas nonweight-bearing passive ankle DF-ROM did not. Improving ankle DF-ROM during the WBL may be an important intervention for altering high-risk movement patterns commonly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
79
2
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(89 citation statements)
references
References 36 publications
(65 reference statements)
3
79
2
5
Order By: Relevance
“…1 Limited dorsiflexion range of motion (DFROM) may contribute to ankle, foot, and knee injuries, including plantar fasciitis, 2,3 ankle sprains, 4 Achilles tendinitis, 5 forefoot pain, 6 navicular stress fractures, 7 calf muscle tightness, 8 Achilles tendinopathy, 9 and anterior cruciate ligament injury. 10 Limited DFROM may be associated with various factors, such as tightness in the plantar flexors (gastrocnemius and soleus), soft tissue and capsular restriction, and loss of accessory motion at the tibiotalar, subtalar, tibiofibular, and midtarsal joints. 11 Posterior gliding of the talus should occur during ankle dorsiflexion (DF) 12,13 ; reduced posterior gliding of the talus can contribute to limited DFROM.…”
mentioning
confidence: 99%
“…1 Limited dorsiflexion range of motion (DFROM) may contribute to ankle, foot, and knee injuries, including plantar fasciitis, 2,3 ankle sprains, 4 Achilles tendinitis, 5 forefoot pain, 6 navicular stress fractures, 7 calf muscle tightness, 8 Achilles tendinopathy, 9 and anterior cruciate ligament injury. 10 Limited DFROM may be associated with various factors, such as tightness in the plantar flexors (gastrocnemius and soleus), soft tissue and capsular restriction, and loss of accessory motion at the tibiotalar, subtalar, tibiofibular, and midtarsal joints. 11 Posterior gliding of the talus should occur during ankle dorsiflexion (DF) 12,13 ; reduced posterior gliding of the talus can contribute to limited DFROM.…”
mentioning
confidence: 99%
“…There is also evidence to suggest that the amount of dorsiflexion available influences knee flexion angle during landing as well as the magnitude of the vertical ground reaction force during the absorption phase. [21][22][23][24] As well, those with CAI demonstrate reduced weight bearing dorsiflexion 25 as well as a talar positional fault 38 due to posterior capsular restrictions in the talocrural joint. Therefore, future studies that examine gait in individuals with CAI should also consider assessing alterations in dorsiflexion range of motion not only to simply increase motion at this individual joint, but to free up the entire lower extremity absorption capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mean differences in this study were only 2.2°, the moderate-to-strong ESs indicate these trends may have clinical implications. Specifically, these trends may reflect functional deficits in force absorption, the transition to propulsion, 22,23 and the transition to a loaded condition for people with CAI. 15 When considering the summary findings, it appears that the cumulative effect of ankle dorsiflexion combined with knee and hip flexion profiles elucidate the functional deficit in those with CAI to a greater extent that any single joint alteration alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Restricted ankle dorsiflexion may also lead to abnormal lower extremity biomechanics during closed chain strengthening exercises4 ) . Backman et al5 ) showed that a low DF ROM in weight-bearing value represents a risk factor for developing patellar tendinopathy in junior elite basketball players because of load-bearing compensation in the patellar tendon.…”
Section: Introductionmentioning
confidence: 99%